Resident Experience Associated with Lung Biopsy Outcomes: A Cross-Sectional Study of Diagnostic Radiology Residents. Does the Level of Training Matter? - Schmanke, Ken; Zackula, Rosalee; Unruh, Zachary; Burdiek, Wesley; Trent, Jesse; Ali, Kamran (Kansas Journal of Medicine, 2020)
Introduction. Efficient execution of image-guided percutaneous biopsy is a procedural competency milestone in radiology training. Despite the importance of achieving such mastery, literature on successful execution by residents is limited. The purpose of this study was to evaluate resident performance as measured by nondiagnostic biopsy and major complication percentages, on CT-guided transthoracic core needle biopsies (TTNB) of lung and mediastinal lesions.Methods. A 12-year retrospective cohort study was conducted using charts from an academic hospital, 2006 - 2018, to evaluate TTNBs. Inclusion criteria were ≥ 18 years of age and ≥ 1 follow-up CT scan and chest x-ray. Bivariable associations by outcome(s) were evaluated.Results. Of 1,191 biopsies conducted, case distribution was 41%, 26%, 18%, and 15% for postgraduate years (PGY) 2 - 5, respectively. Results from biopsies were 139 (11.7%) nondiagnostic, 218 (18.3%) benign, and 834 (70.0%) malignant cases. Resident year by nondiagnostic outcome was not significant; p = 0.430. There were 148 major complications. Complication rate by PGY 2 - 5 was 13.0%, 13.3%, 12.9%, and 9.2%, respectively; differences were not significant, p = 0.488. Of the 139 nondiagnostic cases, 42 were re-biopsied during the study period with 81% re-classified as malignant; no repeat biopsy was observed for the remaining 97 nondiagnostic cases.Conclusion. Of 1,191 lung/mediastinal biopsies analyzed, nearly 12% were nondiagnostic and over 12% had major complications; neither associated with resident level of experience. Outcomes were not affected significantly by level of training. Residency programs may benefit from affording opportunities for newer PGY classes to participate in procedures. Nondiagnostic cases may benefit from timely, repeat biopsies.